Water-Soluble 2D Transition Metal Dichalcogenides as the Hole-Transport Layer for Highly Efficient and Stable p–i–n Perovskite Solar Cells - Huang, Peng; Wang, Zhaowei; Liu, Yanfeng; Zhang, Kaicheng; Yuan, Ligang; Zhou, Yi; Song, Bo; Li, Yongfang (ACS applied materials & interfaces, 2017)
As a hole-transport layer (HTL) material, poly(3,4-ethylenedioxythiophene):polystyrene-sulfonate (PEDOT:PSS) was often criticized for its intrinsic acidity and hygroscopic effect that would in the long run affect the stability of perovskite solar cells (Pero-SCs). As alternatives, herein water-soluble two-dimensional (2D) transition metal dichalcogenides (TMDs), such as MoS2 and WS2 were used as HTLs in p–i–n Pero-SCs. It was found that the content of 1T phase in 2D TMDs HTLs is centrally important to the power conversion efficiencies (PCEs) of Pero-SCs, and the 1T-rich TMDs (as achieved from exfoliation and without postheating) lead to much higher PCEs. More importantly, as PEDOT:PSS was replaced by 2D TMDs, both the PCEs and stability of Pero-SCs were significantly improved. The highest PCEs of 14.35 and 15.00% were obtained for the Pero-SCs with MoS2 and WS2, respectively, whereas the Pero-SCs with PEDOT:PSS showed a highest PCE of only 12.44%. These are up to date the highest PCEs using 2D TMDs as HTLs. After being stored in a glovebox for 56 days, PCEs of the Pero-SCs using MoS2 and WS2 HTLs remained 78 and 72%, respectively, whereas the PCEs of Pero-SCs with PEDOT:PSS almost dropped to 0 over 35 days. This study demonstrates that water-soluble 2D TMDs have great potential for application as new generation of HTLs aiming at high performance and long-term stable Pero-SCs.